Pengaruh Ketersediaan Air Bersih terhadap Keberlangsungan Hidup Masyarakat di Desa Sikalang, Kecamatan Talawi, Kota Sawahlunto - Dea Ananta, Delta; Linda Marni; Jariyanis Sa'adah; Desi Pesti Sari; Madury Enzellorenza Lashwarya; Sofwatul Akhyari (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the influence of clean water availability on the livelihood sustainability of the community in Sikalang Village, Talawi District, Sawahlunto City, as clean water is a vital element affecting public health, economic activities, and social quality. This research employed a descriptive quantitative approach using a four-point Likert scale questionnaire distributed online to local residents. The sample consisted of 34 household representatives selected through a purposive sampling technique, with respondents required to be residents who rely on local clean water sources for daily needs. The collected data were analyzed using descriptive statistics through percentage calculations and frequency distribution tabulation to illustrate accessibility patterns, water quality, and community perceptions. The findings show that 76.47% of respondents have adequate access to clean water, although its distribution remains uneven across the village area. Additionally, 70.58% of respondents reported experiencing health problems due to limitations in clean water access, while 88.24% stated that water availability affects their economic productivity. Meanwhile, community awareness of protecting water sources is relatively high, although government supervision of water quality remains limited. These results indicate that clean water management in Sikalang Village is not yet optimal in terms of equity, quality, and sustainability